Pengaruh Kompetensi Profesional, Sarana Prasarana dan motivasi berprestasi terhadap Kinerja Dosen - Muh. Arif; Darmawang Darmawang; Nahriana Nahriana (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2021)
The study aims at discovering the influence of professional competence, the influence facility and infrastructure on the performance of lecturers, the influence of achievement motivation at Tourism Polytechnic of Makassar. Data collection techniques employed observation, questionnaire, documentation, and interview. The number of samples in this study were 147 people consisting of lecturers and teaching staff with a sample of 114 people. The data analysis technique used is multiple linear regression analysis using the SPSS 22 program to obtain the following research results: (i) based on the statistical calculation results α of X1 is 0.000 less than 0.05 then Ha is rejected and H0 is accepted, which means professional competence X1 turned out to significantly influence the performance of lecturers (Y) at the Makassar Tourism Polytechnic. (ii) Based on the results of statistical calculations, the α value of X2 is 0,000 less than 0.05, then Ha is rejected and Ho is accepted. Thus the infrastructure (X2) significantly influence the performance of lecturers (Y) at the Makassar Tourism Polytechnic. (iii) Based on the statistical calculation results, the α value of X3 is 0,000 less than 0.05, then Ha is rejected and Ho is accepted. Thus the achievement motivation (X3) turned out to have a significant influence on the performance of lecturers (Y). These results indicate that there is a very significant influence between the independent variables X1, X2 and X3 simultaneously on lecturer performance (Y). Thus the first hypothesis which states that professional competence (X.1), infrastructure (X.2), achievement motivation (X.3) simultaneously affect lecturer performance.